A Survey and Influence Study on the Development of Performance Art in Contemporary Chinese Erhu Adaptation Works - Wang, Yubo; Kantasiri, Kovit (Journal of Ecohumanism, 2024)
In recent years, the development of Chinese erhu adaptation works has reached its peak, and there have been many new changes in style and performance. More and more erhu adaptation works are also being presented to the audience on stage. This article aims to study the status of Chinese erhu adaptation works in contemporary erhu music, the impact of erhu performance techniques, and the transformation of erhu performance forms caused by erhu adaptation works. Based on my own professional research experience, the author designed a survey questionnaire on the development status of performance art in erhu adaptation works. The sample is mainly composed of teachers and students majoring in erhu in China. Their actual views on the performance and aesthetics of erhu adaptated works are selected to understand the current development status of erhu adaptated works and provide a basis for analyzing the future development of erhu adaptated works. The tool for collecting data is to distribute survey questionnaires face-to-face, and analyze the data through descriptive statistics and content analysis. The research results are as follows: 1. Instrumental transplantation works account for the largest proportion of erhu adaptation works; 2. the adaptationof erhu works has a positive effect on the improvement of erhu skills; 3. Chinese erhu professional performers are enthusiastic about playing erhu adaptated works.